2020
DOI: 10.1080/23288604.2020.1744988
|View full text |Cite
|
Sign up to set email alerts
|

On the Measurement of Financial Protection: An Assessment of the Usefulness of the Catastrophic Health Expenditure Indicator to Monitor Progress Towards Universal Health Coverage

Abstract: Ensuring financial protection (FP) against health expenditures is a key component of Sustainable Development Goal (SDG) 3.8, which aims to achieve Universal Health Coverage (UHC). While the proportion of households with catastrophic health expenditures exceeding a proportion of their total income or consumption has been adopted as the official SDG indicator, other approaches exist and it is unclear how useful the official indicator is in tracking progress toward the FP subtarget across countries and across tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…We opted to focus our analysis of UHC solely on elements of service coverage, rather than financial risk protection, given the ongoing debate on the measurement challenges associated with current thresholds used in the calculation of the official SDG indicator on financial protection as a component of UHC. [36][37][38] We removed the service capacity and access component as it is conceptually meant to measure the health system functionality component and thus may introduce predictable collinearity. We calculated values for spearman's rho between the emerging functionality scores and the UHC index, postulating that a strong correlation would confer face validity of the emerging index as a good predictor of UHC attainment.…”
Section: Construct Validitymentioning
confidence: 99%
“…We opted to focus our analysis of UHC solely on elements of service coverage, rather than financial risk protection, given the ongoing debate on the measurement challenges associated with current thresholds used in the calculation of the official SDG indicator on financial protection as a component of UHC. [36][37][38] We removed the service capacity and access component as it is conceptually meant to measure the health system functionality component and thus may introduce predictable collinearity. We calculated values for spearman's rho between the emerging functionality scores and the UHC index, postulating that a strong correlation would confer face validity of the emerging index as a good predictor of UHC attainment.…”
Section: Construct Validitymentioning
confidence: 99%
“…Su et al (2006) reported that as much as 14.6-25.7% of the households from the lowest quartile in the general population in Nouna incurred catastrophic healthcare expenditure before the implementation of community-based health insurance [21]. None of these studies measured the extent to which ultra-poor are exposed to financial hardship through the use of health services, despite researchers have highlighted the importance of monitoring such outcome to secure the achievement of the sustainable development goals (SDGs), in particular SDG3, targeting specifically health for all [22]. The lack of evidence on the financial risk protection for the ultra-poor in Burkina Faso is comparable with other low-and middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…This is most significant when patients self-treat since cost rose by about US $7 between 2012 and 2018. The increase in OOPPs and incidence of CHEs can be attributed to the successful implementation of components of these health reforms since studies have suggested that when health reforms improve access to healthcare but does not adequately protect users from OOPPs, the incidence of OOPPs and CHE tend to increase [37,38]. A review of the performance of health systems reforms in the Kyrgyz Republic from independence to 2010 by Ibraimova et.…”
Section: Discussionmentioning
confidence: 99%